2009
DOI: 10.1373/clinchem.2008.115162
|View full text |Cite
|
Sign up to set email alerts
|

Intermethod Variability in TSH-Receptor Antibody Measurement: Implication for the Diagnosis of Graves Disease and for the Follow-Up of Graves Ophthalmopathy

Abstract: BACKGROUND:We compared the analytical and clinical performance of 3 porcine thyroid receptor antibody (TRAb) methods (1 second-and 2 new third-generation systems) with the conventional TRAb assay based on the human recombinant TSH receptor (hTRAK).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 17 publications
0
22
0
1
Order By: Relevance
“…The method is called the manual third-generation TRAb assay. However, the diagnostic accuracy of this manual ELISA is similar to that of the second-generation TRAb assay methods [24,26,[28][29][30][31] ( Table 1). The main limitation of these assays is their poor analytical sensitivity and imprecision due to the manual nature of the procedure.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…The method is called the manual third-generation TRAb assay. However, the diagnostic accuracy of this manual ELISA is similar to that of the second-generation TRAb assay methods [24,26,[28][29][30][31] ( Table 1). The main limitation of these assays is their poor analytical sensitivity and imprecision due to the manual nature of the procedure.…”
Section: Introductionmentioning
confidence: 61%
“…Several studies have shown that the clinical sensitivity of these assays increases to a mean of 95.9% (range 72.6-100%; Table 1) with a small decrease in specificity (97.9%, range 91.4-100%) [15,[17][18][19][22][23][24][25][26][27][28][29][30]. The recombinant human TSHR-based second-generation assay, in combination with labelled bovine TSH, is now considered the gold standard with the highest diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Through first-, second-, and third-generation modification, TBII has been modified to enhance its diagnostic sensitivity and specificity for Graves' disease (GD). [6][7][8] Classical TBII assays are limited by their inability to discriminate between thyroid-stimulating antibodies (TSAbs) and thyroid-blocking antibodies (TBAbs). However, the most newly developed thirdgeneration TBII assay inhibits binding of a labeled TSAb (monoclonal Ab clone #M22) rather than labeled TSH to the TSH receptor 9,10 This results in enhanced sensitivity and specificity vs earlier assays using radiolabeled TSH.…”
Section: Introductionmentioning
confidence: 99%
“…However, the most newly developed thirdgeneration TBII assay inhibits binding of a labeled TSAb (monoclonal Ab clone #M22) rather than labeled TSH to the TSH receptor 9,10 This results in enhanced sensitivity and specificity vs earlier assays using radiolabeled TSH. 6,8,11,12 The TSI bioassay measures cyclic adenosine monophosphate production after TSAb binds to TSH receptor. [13][14][15] Thus, this method enables the identification of the functional characteristics of TRAb.…”
Section: Introductionmentioning
confidence: 99%
“…However, third-generation TRAb assays, which use the monoclonal thyroid-stimulating antibody M22 labeled either with biotin in ELISAs or with ruthenium in the automated Elecsys®/Cobas®, have also been developed. It is now established that these third-generation assays have no clinical advantages over second-generation methods in the diagnosis (2,3 ) or in the follow-up of Graves disease patients (4 ). Recently, it has been reported that the automated third-generation TRAb assays should be performed on clinical chemistry platforms and should prompt appropriate revision of the current thyroid guidelines (2 ).…”
mentioning
confidence: 99%